Evidence of a Causal Relationship Between Smoking Tobacco and Schizophrenia Spectrum Disorders - Scott, James G.; Matuschka, Lori; Niemelä, Solja; Miettunen, Jouko; Emmerson, Brett; Mustonen, Antti (Frontiers in Psychiatry, 2018)
There has been emerging evidence of an association between tobacco smoking and schizophrenia spectrum disorders. Two meta-analyses have reported that people who smoke tobacco have an approximately twofold increased risk of incident schizophrenia or psychosis, even after adjusting for confounding factors. This study aimed to critically appraise the research which has examined the association between tobacco smoking and schizophrenia spectrum disorders against the Bradford Hill criteria for causality, to determine the strength of the evidence for a causal relationship. Eight longitudinal studies (seven cohort studies and one case control study) were identified which examined tobacco smoking as an exposure and psychosis as an outcome. All seven cohort studies were assessed as being of high quality using the Newcastle-Ottawa Scale. Six of the eight studies found a statistically significant positive association between tobacco smoking and onset of schizophrenia spectrum disorder. These studies reported a consistent association with a moderate to large effect size and a dose response relationship. The studies adjusted for multiple potential confounders including age, sex, socioeconomic status, shared genetic risk, prodromal symptoms and comorbid cannabis and other substance use. The studies did not adjust for exposure to childhood trauma or prenatal tobacco. There was substantial though inconclusive evidence supporting a causal relationship between tobacco smoking and increased risk of schizophrenia spectrum disorders. If a causal relationship does exist, nicotine is most likely responsible for this association. This raises serious public health concerns about the increasing use of e-cigarettes and other products, particularly by adolescents whose nicotine use may increase their risk of schizophrenia spectrum disorders. Research is urgently needed to examine the association between e-cigarette use and incident psychosis, particularly in adolescents and young adults.